Territorial competition in Mexico, regional performance and the role of federal transfers - Alejandra Trejo; Cristina Ibarra (European Regional Science Association (ERSA), 2011)
In an environment of growing globalization, which goes along with a relative increase of factor mobility, the role of territories and its competitiveness is under debate. In order to spur local attraction territories often enter in competition with each other. At this respect it is commonplace that governments at various territorial levels apart from other public and private institutions concern about providing the conditions that make attractive their countries, regions or cities for productive activities and in so doing they get involved in the race for competitiveness. Even though competition involves the actions of multiple actors, these often are connected with each other through local policy makers. By and large, local government and regional development policy are regarded to play a central function in territorial competition and in fact can be considered that the competitive success of regions and cities cannot be achieved without the active action of local governments. To the extent to which governments are more conscious about the actual territorial competitive environment they will try to formulate more policies for the development of competitive capabilities. The actions and efforts may take many forms (marketing, assisting local businesses, constructing infrastructure, information and land provision, taxation and so on). Particularly governments may use programs or apply funds, which are available as a result of national or regional policy, to attend to local interests. However local governments' actions depend to a large extent on their financial capabilities. The federal government in Mexico provides most of the financial support to states and municipalities on an ongoing basis through transfers and participations. These are federal transfers supporting specific policy areas or unconditional transfers.This paper is concerned with presenting an integrated framework for territorial competition analysis which emphasises the fundamental role of local government action and assessing the role of federal aid on the competitive results of Mexican regions. The methodology proposed will develop a series of competitive results indicators for Mexican regions and use a multivariate analysis to assess the influence of transfers and participations. The periods include those years when Mexico has been and opened and liberalised economy.
Keywords: 330